Sensory characteristics of monkey thalamic and motor cortex neurones. - Butler, E G (1992)
1. Extracellular single-cell recordings were made from the cerebellar thalamus, the ventro-posterior lateralis par caudalis (VPLc) and motor cortex of three conscious monkeys. Recordings were made from the thalamus as well as the cortex in two monkeys. In all, recordings were made from the thalamus in four hemispheres and from the motor cortex in four hemispheres. The animals were trained to permit a detailed examination when relaxed. Unexpected perturbations were applied to the wrist. Seventy-seven wrist-related neurones were recorded in the cerebellar thalamus, forty-two neurones from the VPLc and eighty-four neurones in motor cortex. 2. Cerebellar nuclear stimulation was used to physiologically identify thalamic neurones receiving input from the cerebellum. The location of all neurones was verified histologically. 3. The majority of cerebellar thalamic neurones had deep sensory receptive fields related to a single muscle, a group of synergists or a single joint. There was a distinct topographical organization. These fields were similar to sensory fields in motor cortical neurones, but had higher thresholds. 4. VPLc neurones had discrete deep or cutaneous sensory fields, or a combination of these fields, which suggests convergence. VPLc neurones had fields with lower thresholds than cerebellar thalamic neurones. The somatotopically located forelimb area in the VPLc was posterior to and continuous with the forelimb area in the cerebellar thalamus. 5. VPLc neurones responded with a shorter latency to wrist perturbations than did cerebellar thalamic neurones. VPLc neurones with deep sensory fields changed firing significantly earlier than those with cutaneous fields. The VPLc is likely to be the major source of sensory input to the motor cortex, and based on the results of this study we suggest that the VPLc is the thalamic nucleus best placed to transmit short-latency afferent input from the forelimb. 6. The timing of the neuronal discharge of cerebellar thalamic and VPLc cells, which resulted from perturbations of the wrist, was best linked to the duration of movement rather than its amplitude. The cells began firing as soon as the velocity changed sign and continued firing until the sign of the velocity changed again. In subsequent corrective movements neuronal discharge in the VPLc appeared to also encode movement acceleration.